Connecting with students online : strategies for remote teaching & learning - Serravallo, Jennifer (Portsmouth, New Hampshire : Heinemann, 2020)
"The professional development for online teaching and learning that you've been asking for. An unprecedented pandemic may take the teacher out of the classroom, but it doesn't take the classroom out of the teacher! Now that you're making the shift to online teaching, it's time to answer your biggest questions about remote, digitally based instruction: How do I build and nurture relationships with students and their at-home adults from afar? How do I adapt my best teaching to an online setting? How do I keep a focus on students and their needs when they aren't in front of me? Jennifer Serravallo's Connecting with Students Online gives you concise, doable answers based on her own experiences and those of the teachers, administrators, and coaches she has communicated with during the pandemic. Focusing on the vital importance of the teacher-student connection, Jen guides you to: Effectively prioritize what matters most during remote, online instruction ; schedule your day and your students' to maximize teaching and learning (and avoid burnout) ; Streamline curricular units and roll them out digitally ; Record highly engaging short lessons that students will enjoy and learn from ; Confer, work with small groups, and drive learning through independent practice ; Partner with the adults in a student's home to support your work with their child. Featuring simplified, commonsense suggestions, 55 step-by-step teaching strategies, and video examples of Jen conferring and working with small groups, Connecting with Students Online helps new teachers, teachers new to technology, or anyone who wants to better understand the essence of effective online instruction. Along the way Jen addresses crucial topics including assessment and progress monitoring, student engagement and accountability, using anchor charts and visuals, getting books into students' hands, teaching subject-area content, and avoiding teacher burnout. During this pandemic crisis turn to one of education's most trusted teaching voices to help you restart or maintain students' progress. Jennifer Serravallo's Connecting with Students Online is of-the-moment, grounded in important research, informed by experience, and designed to get you teaching well -- and confidently -- as quickly as possible"--Provided by publisher
Holding True to Priorities as We Move Online -- Partnering with Adults at Home -- Planning and Revising Curriculum Units for Online Instruction -- Managing Your Time Across a Day, Across the Week -- Setting Up Students' Independent Practice at Home -- Methods and Structures for Teaching Online.
Includes bibliographical references.
Keywords: Teaching -- Computer network resources; Web-based instruction; Computer-assisted instruction; Computer managed instruction; Educational technology; Computers and literacy; Internet in education; Distance education; Computer-assisted instruction; Computer managed instruction; Computers and literacy; Distance education; Educational technology; Internet in education; Teaching -- Computer network resources; Web-based instruction; Handbooks and manuals; Handbooks and manuals